Real World Data on Forgiveness to Uncomplete Adherence to Bictegravir/ Emtricitabine/Tenofovir Alafenamide. (November 2022) - Maggiolo, Franco; Valenti, Daniela; Teocchi, Rodolfo; Comi, Laura; Di Filippo, Elisa; Rizzi, Marco
Background: forgiveness is the ability of a given regimen to maintain complete viral suppression despite a documented imperfect adherence. We explored forgiveness of bictegravir/emtricitabine/tenofovir alafenamide.Methods: drug refills were used to calculate the percent day covered (PDC) as a proxy of adherence. Forgiveness was calculated as the achieved rate of a selected HIV-RNA threshold by a given level of imperfect adherence.Results: 281 adult PLWH were followed for 343 patient/years. Adherence was very high with a median of 98% (IQR 95-100%). A PDC as low as 70% was sufficient to obtain 100% and maintain virologic suppression. According to probit analysis adherence was not related to the possibility to maintain an HIV-RNA TND or < 50 copies/ml.Conclusions: Long-term success of ART needs effective regimens that are the least intrusive of the patient's lifestyle, an elevated forgiveness may be considered as an additional feature that can further improve long-term outcomes.